The model of gas discharge sustained by the quadrupole electromagnetic wave in waveguide structure with varying radius of metal enclosure - Azarenkov, N.A.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2019)
This article presents the results of the theoretical study of stationary state of gas discharge sustained by the electromagnetic wave with azimuth wavenumber m=−2 in three component magnetized plasma-metal waveguide structure of slightly varying radius of metal enclosure in the framework of electromagnetic model. It was studied the influence of the external magnetic field value, the electron effective collision frequency and other parameters on the phase characteristics, spatial attenuation, discharge stability and axial plasma density profile in the structure with constant radius of metal waveguide and with radius that varies slightly along the discharge. Представлено результати теоретичного дослідження в рамках електромагнітної моделі стаціонарного газового розряду, що підтримується електромагнітною хвилею з азимутальним хвильовим числом m =−2 у трикомпонентній магнітоактивній плазмово-металевій хвилеводній структурі з радіусом металевого кожуху, що слабко змінюється вздовж розряду. Вивчено вплив зовнішнього магнітного поля, ефективної частоти зіткнень електронів та інших параметрів на фазові характеристики, просторове загасання, стабільність розряду та аксіальний профіль густини плазми в структурі з незмінним радіусом металевого хвилеводу та з таким, що слабко змінюється уздовж розряду. Представлены результаты теоретического исследования в рамках электромагнитной модели стационарного газового разряда, поддерживаемого электромагнитной волной с азимутальным волновым числом m =−2 в трехкомпонентной магнитоактивной плазменно-металлической волноводной структуре со слабо изменяющимся вдоль разряда радиусом металлического кожуха. Изучено влияние внешнего магнитного поля, эффективной частоты столкновений электронов и других параметров на фазовые характеристики, пространственное затухание, стабильность разряда и аксиальный профиль плотности плазмы в структуре с постоянным радиусом металлического волновода и слабо изменяющимся вдоль разряда.